Posterior Fossa Craniotomy for Adherent Fourth Ventricle Neurocysticercosis. Issue 5 (14th June 2018) - Franko, Lynze R; Pandian, Balaji; Gupta, Avneesh; Savastano, Luis E; Chen, Kevin S; Riddell, James; Orringer, Daniel A
Abstract: BACKGROUND AND IMPORTANCE: Neurocysticercosis (NCC) is an infectious helminthic disease often presenting in patients who have immigration or travel history from areas where NCC is endemic. Fourth ventricle cysts from NCC pose a unique treatment challenge, as there is little consensus on the best treatment. This case study describes the treatment of a patient with fourth ventricle neurocysticercosis (FVNCC), examines the therapeutic decision-making, and provides a video of a posterior fossa craniotomy (PFC) resection of a degenerative cyst. CLINICAL PRESENTATION: The patient presented with headache, dizziness, nausea, and memory difficulties. A fourth ventricle cyst consistent with NCC was found on magnetic resonance imaging, and serum enzyme-linked immunosorbent assay (ELISA) confirmed the diagnosis. The cyst was removed utilizing an open PFC followed by antihelminthic therapy and corticosteroids. There was resolution of symptoms at 9 mo postoperatively. CONCLUSION: Several treatment modalities have been proposed for isolated cysts in the fourth ventricle, including medication, ventriculoperitoneal shunt, endoscopic removal, and PFC. The treatment decision is complex, and there is little guidance on the best treatment choices. In this article, we describe treatment via PFC for an adherent FVNCC cyst.